Early outcomes of primary total hip arthroplasty with use of a smartphone-based care platform: a prospective randomized controlled trial. (7th July 2021) - Crawford, David A.; Lombardi, Adolph V.; Berend, Keith R.; Huddleston, James I.; Peters, Christopher L.; DeHaan, Alexander; Zimmerman, Erin K.; Duwelius, Paul J.
Abstract : Aims: The purpose of this study is to evaluate early outcomes with the use of a smartphone-based exercise and educational care management system after total hip arthroplasty (THA) and demonstrate decreased use of in-person physiotherapy (PT). Methods: A multicentre, prospective randomized controlled trial was conducted to evaluate a smartphone-based care platform for primary THA. Patients randomized to the control group (198) received the institution's standard of care. Those randomized to the treatment group (167) were provided with a smartwatch and smartphone application. PT use, THA complications, readmissions, emergency department/urgent care visits, and physician office visits were evaluated. Outcome scores include the Hip disability and Osteoarthritis Outcome Score (HOOS, JR), health-related quality-of-life EuroQol five-dimension five-level score (EQ-5D-5L), single leg stance (SLS) test, and the Timed Up and Go (TUG) test. Results: The control group was significantly younger by a mean 3.0 years (SD 9.8 for control, 10.4 for treatment group; p = 0.007), but there were no significant differences between groups in BMI, sex, or preoperative diagnosis. Postoperative PT use was significantly lower in the treatment group (34%) than in the control group (55.4%; p = 0.001). There were no statistically significant differences in complications, readmissions, or outpatient visits. The 90-day outcomes showed no significant differences in mean hip flexion between controls (101° (SD 10.8)) and treatment (100° (SD 11.3); p = 0.507) groups. The HOOS, JR scores were not significantly different between control group (73 points (SD 13.8)) and treatment group (73.6 points (SD 13); p = 0.660). Mean 30-day SLS time was 22.9 seconds (SD 19.8) in the control group and 20.7 seconds (SD 19.5) in the treatment group (p = 0.342). Mean TUG time was 11.8 seconds (SD 5.1) for the control group and 11.9 (SD 5) seconds for the treatment group (p = 0.859). Conclusion: The use of the smartphone care management system demonstrated similar early outcomes to those achieved using traditional care models, along with a significant decrease in PT use. Noninferiority was demonstrated with regard to complications, readmissions, and ED and urgent care visits. This technology allows patients to rehabilitate on a more flexible schedule and avoid unnecessary healthcare visits, as well as potentially reducing overall healthcare costs. Cite this article: Bone Joint J  2021;103-B(7 Supple B):91–97.